Evaluation of Piper betle on Platelet Activating Factor (PAF) Receptor Binding Activities - Md. Pisar, Mazura; Hashim, Nuziah; Mat Ali, Rasadah; L.S, Kiong (Malaysian Journal of Science, 2007)
Betel vine (Piper betle) is a tropical Asian plant belonging to the family Piperaceae. It is a vine that has long held a place in Asian history, religion and culture. Its medicinal uses are many and all parts of the plants are utilized. As part of our research programme into the exploitation of natural sources for their biological activities, various extracts of P. betle from 2 different locations (i.e. Pahang and Melaka) were screened for antagonist activity towards [³H]-PAF (platelet activating factor) in washed rabbit platelet receptor binding studies. The methanolic extract of leaves from each location were suspended in water and partitioned with hexane, dichloromethane and ethyl acetate. Our results showed that the activity towards inhibition of [³H]-PAF receptor binding was pinpointed to be in dichloromethane fraction from Melaka. Further purification of this fraction revealed hydroxychavicol as the main component involved in its anti-inflammatory activity.